IMATINIB IN CHRONIC MYELOID LEUKEMIA: AN OVERVIEW - Tomasz Sacha (Mediterranean Journal of Hematology and Infectious Diseases, 2013)
Imatinib was the first signal transduction inhibitor (STI), used in a clinical setting. It prevents a BCR-ABL protein from exerting its role in the oncogenic pathway in chronic myeloid leukemia (CML). Imatinib directly inhibits the constitutive tyrosine kinase activity. Imatinib binds to BCR-ABL kinase domain by preventing the transfer of a phosphate group to tyrosine on the protein substrate and the subsequent activation of phosphorylated protein. As the result, the transmission of proliferative signals to the nucleus is blocked and leukemic cell apoptosis is induced. The FDA has approved imatinib as first-line treatment for newly diagnosed CML in December 2002 following an International Randomized Study (IRIS), initiated in June 2000, comparing imatinib at a single daily dose 400 mg to IFN alpha plus cytarabine in newly diagnosed patients with CML in CP. Results from this study show the outstanding effectiveness of imatinib and its superiority with respect to the rates of complete hematological response (CHR), major and complete cytogenetic response (MCyR, CCyR). Patients randomized to imatinib arm at 8 – year data cut off continue to have a durable hematologic and cytogenetic response, low progression rates to AP or BC, and remarkable survival outcomes. An overall survival (OS) rate is 85% for patients receiving imatinib (93% when only CML-related deaths and those prior to stem cell transplantation are considered). The results have been confirmed in the last years by several groups. According these cumulative results the rates of CCyR achieved after one year of therapy with imatinib at standard dose ranged from 49% to 77%, and the proportion of patients who achieved major molecular response (MMR) after one year ranged between 18% and 58%. Discontinuation of imatinib has been also tried in patients in MMR, a molecular relapse occurs in about one third of patients, generally within 6 months from imatinib cessation.